Fiscal consequences of paying interest on reserves - Marco Bassetto; Todd Messer (Federal Reserve Bank of Chicago, 2013)
We review the role of the central bank's (CB) balance sheet in a textbook monetary model, and explore what changes if the central bank is allowed to pay interest on its liabilities. When the central bank cannot pay interest, away from the zero lower bound its (real) balance sheet is limited by the demand for money. Furthermore, if securities are not marked to market and the central bank holds its bonds to maturity, it is impossible for the central bank to make losses, and it always obtains profits from being a monopoly provider of money. When the option of paying interest on liabilities is allowed, the limit on the CB's balance sheet is lifted. In this case, the CB is free to take on interest rate risk, e.g, by buying long-term securities and financing those purchases with short-term debt that pays the market interest rate. This is a risky enterprise that can lead to additional profits but also to losses. To the extent that losses exceed the profits of the monopoly operations, the CB faces two options: either it is recapitalized by Treasury, or it increases its monopoly profits by raising the inflation tax.
Keywords: 330